Presença de fatores de risco dependentes ou não de esforço físico em praticantes de corrida de rua - Ishida, Jaqueline de Castro [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
In order to reduce the sedentarism and to improve population's health condition, many physical activity incentive programs have been stimulated. As a result, many people have adhered to street racing, but their health condition is almost always ignored. The aim of this study was to evaluate street racers' health condition, identifying the presence of cardiovascular risk factors as well as problems associated to street racing. The study case was composed by 111 racers from the town of Bauru (94 men and 17 women) aged in average 39±13 years old, who were evaluated in 4 street race competitions. The subjects answered to an anamnesis with questions about their socioeconomic status, medicine use, cardiovascular risk, physical exercise practices, and issues related to racing and injury. Weight (kg) and height (m) were measured to calculate the body mass index (BMI, kg/m²) as well as systolic and diastolic blood pressure (BP), heart rate (HR), abdominal circumference (AC), and flexibility. It could be observed that the majority of racers were Caucasian, married and belonged to social classes over C. The prevalent age was between 18 and 35 years old (42%). Among the participants, 38.7% have already undergone some kind of surgery and 13% declared having some health problem. The questionnaire pointed out that 36% had low and moderate cardiovascular risk. It could be noticed from the AC that 10% of men and 18% of women had high cardiac risk. Among the tested, 43.2% (24.3% altered and 18.9% borderline) showed high BP on the day of the test, but only 2.7% had self-declared hypertensive. In relation to injury, 36% had already had lesions of some kind, 27.5% of which had occurred in the last 8 months. 66.6% had derived from training or racing competitions and the knee was the mostly affected body part. Only 43% had professional orientation by a physical education teacher during their training and the main reasons for them to begin racing practice were...

Com o intuito de reduzir o índice de sedentarismo e melhorar a condição de saúde da população, diversos programas de incentivo à atividade física têm sido estimulados. Como resultado, muitas pessoas têm aderido à corrida de rua, no entanto, a condição de saúde desta população quase sempre é ignorada. O objetivo deste estudo foi avaliar a condição de saúde de corredores de rua, identificando a presença de fatores de riscos cardiovasculares e problemas associados às corridas de rua. A casuística do estudo foi constituída de 111 corredores (94 homens e 17 mulheres) com idade média 39±13 anos da cidade de Bauru, avaliados em um total de 4 provas de corrida de rua. Os indivíduos responderam uma anamnese com questões sobre condição socioeconômica, uso de medicamentos, risco cardiovascular, prática de exercícios físicos, questões específicas sobre corrida e lesão. Foram avaliados o peso (kg) e altura (m), para cálculo do índice de massa corporal (IMC, kg/m²), pressão arterial (PA) sistólica e diastólica, frequência cardíaca (FC) de repouso, circunferência abdominal (CA) e flexibilidade. Pode-se observar que os corredores são em sua maioria brancos, casados e pertencem a classes sociais superiores a C, cuja idade mais prevalente foi de 18 a 35 anos (42%). Dos participantes, 38,7% já passaram por alguma cirurgia e 13% declararam ter algum problema de saúde. O questionário apontou que 36,9% possuíam risco cardiovascular baixo e moderado. Pode-se observar que pela CA, 10% dos homens e 18% das mulheres possuíam risco cardíaco elevado. Dentre os avaliados, 43,2% (24,3% elevada e 18,9% limítrofe) estavam com a PA alterada no dia da avaliação e somente 2,7% haviam se declarado hipertensos. Em relação à lesão, 36% dos participantes já sofreram algum tipo, sendo que destes, 27,5% ocorreram nos últimos 8 meses e 66,6% foram derivadas de treino ou competições de corrida, sendo o joelho o membro mais...
Keywords: Corredores (Esportes); Estilo de vida sedentário; Corridas; Avaliação de resultados (Cuidados médicos); Caminhada; Traumatismos em atletas; Runners (Sports)